Whole genome sequence of multidrug-resistant Staphylococcus haemolyticus and Enterococcus faecalis isolates from public gymnasium equipment reveals evolving infection potential and resistance - Goutam Banerjee; Pratik Banerjee (PLoS ONE, 2025)
Whole genome sequences (WGSs) of Enterococcus fa ecalis S3 and S taphylococ cus haemolyticus S5, isolated from gymnasium equipment in Tennessee, USA, were analyzed. The genome sizes of E. faecalis S3 and S. haemolyticus S5 were approximately 3.0 Mb and 2.5 Mb, respectively. Both isolates were found to harbor genes conferring resistance to multiple antibiotics, including tetracycline, fluoroquinolone, and macrolide. Gene cluster analysis revealed a cyclic lactone inducer cluster in both strains, which is critical for quorum sensing-mediated pathogenicity. Multilocus sequence typing (MLST) identified E. faecalis S3 as ST40 and S. haemolyticus S5 as ST52. Notably, evolutionary analysis of gene contraction and expansion in these isolates revealed an expansion of genes associated with horizontal gene transfer. This expansion likely represents an evolutionary strategy to facilitate the spread of antibiotic resistance genes to other isolates. These findings offer valuable insights into the genomic apparatus responsible for antibiotic resistance and potential transmission mechanisms in human-associated environments.